Impact of Public Information Arrivals on Cryptocurrency Market: A Case of Twitter Posts on Ripple - Samet Gunay (East Asian Economic Review (EAER), 2019)
Public information arrivals and their immediate incorporation in asset price is a key component of semi-strong form of the Efficient Market Hypothesis. In this study, we explore the impact of public information arrivals on cryptocurrency market via Twitter posts. The empirical analysis was conducted through various methods including Kapetanios unit root test, Maki cointegration analysis and Markov regime switching regression analysis. Results indicate that while in bull market positive public information arrivals have a positive influence on Ripple's value; in bear market, however, even if the company releases good news, it does not divert out the Ripple from downward trend.
Keywords: G14; G15; G40; G41; 330; Cryptocurrency; Public Information Arrivals; Semi-Strong Efficiency; Ripple; Twitter Posts